Intervalos de confiança para dados com presença de eventos recorrentes e censuras - Faria, Rodrigo (2003)
In survival analysis and reliability is common that the population units in study presents recurrence events and censoring ages, besides, is possible to exist a cost related to each event that happens. The objectives of this dissertation consists in display a methodology that makes possible the direct obtaining of confidence intervals baseds in asymptotic theory for nonparametric estimates to the mean cumulative number or cost events per unit. Some simulation studies are also showed and the objectives are check if there is some sample size's influence in the asymptotics confidence interval's precision. One of the great advantages from the methodology presented in this dissertation is the validity for it’s application in several areas of the knowledge. There's two examples considered here. One of them consists in coming data from engineering. This example contains a ‡eet of machines in analysis. The interest is to obtain punctual estimates with the respective confidence intervals for the mean cumulative number and cost repairs per machine. The other example comes from the medical area and it treats of a study accomplished with two groups of patients with bladder can- cer, each one submitted in a di¤erent treatment type. The application of the methodology in this example seeks the obtaining of confidence intervals for the mean cumulative number of tumors per patient and gain estimates that compare these two di¤erents treatments informing, statistically, which presents better results.